Development of Interactive PowerPoint Media to Improve Science Learning Outcomes of Grade V Students of SDN 2 Gumulan Academic Year 2024/2025 - Nova Sugiana Purwaningrum; Isna Rahmawati; Nela Rofisian (Badan Penerbit STIEPARI Press, 2025)
This study aims to create and evaluate interactive PowerPoint learning media used to help fifth grade students at SDN 2 Gumulan to understand lessons more easily and improve learning outcomes. The problems faced are low learning motivation and monotonous teaching methods for science. As a solution, interactive PowerPoint media is used for fifth grade science material, Chapter 6